Diet and exercise improve chemoreflex sensitivity in patients with metabolic syndrome and obstructive sleep apnea. (6th July 2015) - Maki‐Nunes, Cristiane; Toschi‐Dias, Edgar; Cepeda, Felipe X.; Rondon, Maria Urbana P.B.; Alves, Maria‐Janieire N. N.; Fraga, Raffael F.; Braga, Ana Maria F. W.; Aguilar, Adriana M.; Amaro, Aline C.; Drager, Luciano F.; Lorenzi‐Filho, Geraldo; Negrão, Carlos E.; et al.
Abstract : Objective: Chemoreflex hypersensitity was caused by obstructive sleep apnea (OSA) in patients with metabolic syndrome (MetS). This study tested the hypothesis that hypocaloric diet and exercise training (D+ET) would improve peripheral and central chemoreflex sensitivity in patients with MetS and OSA. Methods: Patients were assigned to: (1) D+ET ( n  = 16) and (2) no intervention control (C, n  = 8). Minute ventilation (VE, pre‐calibrated pneumotachograph) and muscle sympathetic nerve activity (MSNA, microneurography) were evaluated during peripheral chemoreflex sensitivity by inhalation of 10% O2 and 90% N2 with CO2 titrated and central chemoreflex by 7% CO2 and 93% O2 for 3 min at study entry and after 4 months. Results: Peak VO2 was increased by D+ET; body weight, waist circumference, glucose levels, systolic/diastolic blood pressure, and apnea–hypopnea index (AHI) (34 ± 5.1 vs. 18 ± 3.2 events/h, P  = 0.04) were reduced by D+ET. MSNA was reduced by D+ET at rest and in response to hypoxia (8.6 ± 1.2 vs. 5.4 ± 0.6 bursts/min, P  = 0.02), and VE in response to hypercapnia (14.8 ± 3.9 vs. 9.1 ± 1.2 l/min, P  = 0.02). No changes were found in the C group. A positive correlation was found between AHI and MSNA absolute changes ( R  = 0.51, P  = 0.01) and body weight and AHI absolute changes ( R  = 0.69, P  < 0.001). Conclusions: Sympathetic peripheral and ventilatory central chemoreflex sensitivity was improved by D+ET in MetS+OSA patients, which may be associated with improvement in sleep pattern.